Association between epicardial adipose tissue and embolic stroke after catheter ablation of atrial fibrillation. (19th September 2019) - Ahn, Jinhee; Shin, Seung Yong; Shim, Jaemin; Kim, Young‐Hoon; Han, Sang‐Jin; Choi, Eue‐Keun; Oh, Seil; Shin, Ji Yeon; Choe, Jeong Cheon; Park, Jin Sup; Lee, Hye Won; Oh, Jun‐Hyok; et al.
Abstract: Introduction: Risk factors of embolic stroke (ES) after atrial fibrillation (AF) ablation have not been fully elucidated especially among the Asian subjects, particularly regarding epicardial adipose tissue (EAT) in cardiac imaging. We aimed to assess the incidence of ES during a long‐term follow‐up period after AF ablation and to identify the risk factors associated with postablation ES, specifically focusing on EAT. Methods and Results: We enrolled patients who experienced postablation ES and control subjects from a consortium of AF ablation registries from three institutes in Korea. EAT was assessed using multislice computed tomography before AF ablation. A total of 3464 patients who underwent AF ablation were recruited and followed‐up. During a follow‐up of 47.2 ± 36.4 months, ES occurred in 47 patients (1.36%) with a CHA2 DS2 ‐VASc score of 1.48 ± 1.39 and the overall annual incidence of ES was 0.34%. Compared with the control group (n = 190), the ES group showed significantly higher prior thromboembolism (TE) and AF recurrence rates, larger left atrium size, lower creatinine clearance rate (CCr), and greater total and peri‐atrial EAT volume. Multivariate regression analysis demonstrated larger peri‐atrial EAT volume (hazards ratio, 1.065; 95% confidence interval, 1.005‐1.128), in addition to a prior history of TE and lower CCr, was independently associated with postablation ES. When a cut‐off value of peri‐atrial EAT volume of ≥20.15 mL was applied, patients with smaller peri‐atrial EAT volume showed significantly higher ES‐free survival. Conclusion: Larger peri‐atrial EAT volume, in addition to prior TE and lower CCr, was independently associated with postablation ES regardless of AF recurrence and CHA2 DS2 ‐VASc score. (ClinicalTrials.gov number, NCT03479073).